1992
DOI: 10.1007/bf01201872
|View full text |Cite
|
Sign up to set email alerts
|

Use of starter cultures containingStreptococcus diacetilactis, Lactobacillus brevis andSaccharomyces cerevisiae for fermenting milk for production of Nigeriannono

Abstract: Starter cultures consisting ofStreptococcus diacetilactis, Strept. cremoris, Lactobacillus brevis andSaccharomyces cerevisiae were tested singly and in mixtures for ability to ferment milk to producenono with organoleptically acceptable qualities. Only mixed cultures containing eitherStrept. diacetilactis orStrept. cremoris andL. brevis were suitable. Presence of yeast adversely affected either acid formation or diacetyl production.Nono containingStrept. diacetilactis was acceptable, even in the presence ofSac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…Our findings are in accordance with Ao et al. (2012) and Okagbue and Bankole (2000) as reported that adding S. cerevisiae had no significant difference through storage.…”
Section: Resultssupporting
confidence: 93%
“…Our findings are in accordance with Ao et al. (2012) and Okagbue and Bankole (2000) as reported that adding S. cerevisiae had no significant difference through storage.…”
Section: Resultssupporting
confidence: 93%
“…cerevisiae has also been reported to be involved in fermentation of 'nono', a Nigerian fermented milk product [49], and 'mbanik' a Senegalese cultured milk product [50]. cerevisiae has also been reported to be involved in fermentation of 'nono', a Nigerian fermented milk product [49], and 'mbanik' a Senegalese cultured milk product [50].…”
Section: Fermented Milkmentioning
confidence: 99%
“…S. cerevisiae has also been reported to be involved in fermentation of 'nono', a Nigerian fermented milk product [49], and 'mbanik' a Senegalese cultured milk product [50]. Saccharomyces spp.…”
Section: Fermented Milkmentioning
confidence: 99%
“…Mixed cultures of S. cerevisiae and L. brevis inoculated during controlled fermentation of cereals for the production ogi gives a product with appealing aroma (Teniola & Odunfa, 2001). Okagbue and Bankole (1992) and Odunfa and Oyewole (1997) reported the occurrence and dominance of S. cerevisiae during fermentation of traditional beverages. Padonou et al (2009) also investigated the microbiology of fermented cassava for production of lafun and reported that L. fermentum, L. plantarum and W. confusa were LAB species isolated during the fermentation process, Kluyveromyces marxianus, Pichia scutulata, and Hansenia guilliermondii were also implicated.…”
Section: Food and Beverage Fermentation By Lab And Yeastsmentioning
confidence: 99%